The hybrid absorption cooling–desalination and reverse osmosis system to boost energy utilization efficiency - Bahram Jalili; Amirhossein Rezaeian; Payam Jalili; Davood Domiri Ganji (Energy Reports, 2023)
The reverse osmosis (RO) process is the most widely used water softening system, which is used due to its high-performance efficiency. However, this method causes damage to the ecosystem by producing concentrated salt water. This research investigated the integration of the newly proposed absorption cooling–desalination (ACD) hybrid system and the reverse osmosis method. In this method, the brine that comes out of the reverse osmosis is introduced to the evaporator of the ACD system for further distillation. This work is a possible solution for the treatment of reverse osmosis output brine, increasing the recovery rate, minimizing the overall cost of operation, and preserving the ecosystem. Also, by the implementation of this novel unit, excessive cold fresh water is created. The results show that the cooling capacity of the ACD system alone is about 0.346 kW with a coefficient of performance (COP) of 0.774, and it can produce 13.887 cubic meters of water per day at a working temperature of 85 degrees Celsius, which can be easily obtained from low-temperature sources. Compared to the reverse osmosis method alone, the combined method of reverse osmosis and ACD unit proposed in this article causes an overall increase in recovery rate (RR) by 72% and a reduction in electrical energy consumption by 49%. Besides, the overall produced water salinity declined by 59% due to the integration of RO and ACD units.